Kajian Minat Membaca Siswa Terhadap Karya Sastra: Study of Students' Reading Interest in Literary Works - Mandarani, Vidya; Nuroh, Ermawati Zulikhatin (Universitas Muhammadiyah Sidoarjo, 2017)
Efforts to increase interest in reading are necessary to cultivate children's interest in reading, as a habit from children till adults. This research is to know the reading interests of students to literature, it is expected that we can provide facilities to children to choose books children's literature that became a favorite to increase reading interests. The study was conducted on a fifth grade students of SD Muhammadiyah 1 Sidoarjo which aims to find out how the students' interest in reading literature. This research uses descriptive qualitative design, with the population students of SD Muhammadiyah 1 Sidoarjo. The sample in this study is a fifth grade elementary school student SD Muhammadiyah 1 Sidoarjo. Collecting data in this study are using methods or techniques of questionnaires, interviews and observation. The results of the study most students like to read picture books or comics, with ownership of books 6-15 books. The students spent time reading about 0-60 minutes a day.